Existence of Solutions to a Class of Semilinear Elliptic Problem with Nonlinear Singular Terms and Variable Exponent - Ying Chu; Yanchao Gao; Wenjie Gao (Journal of Function Spaces)
The authors of this paper prove the existence and regularity results for the homogeneous Dirichlet boundary value problem to the equation - div(M(x)∇un)=f(x)/uα(x) with f∈Lm(Ω)  (m⩾1) and α(x)>0. The results show the dependence of the summability of f in some Lebesgue spaces and on the values of α(x).